Revolutionizing IRU Accounting: The Integration of AI in ERP Systems - Eswar Sanka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article explores the transformative impact of Artificial Intelligence integration within Enterprise Resource Planning systems for managing Indefeasible Right of Use accounting. The article examines how AI-driven solutions address traditional challenges in IRU accounting while introducing innovative approaches to asset classification, revenue recognition, and compliance management. Through a comprehensive article of implementation frameworks, advanced features, and future developments, this article demonstrates how machine learning algorithms, predictive analytics, and automated processes are revolutionizing financial management practices while ensuring regulatory compliance across multiple jurisdictions. The article highlights significant improvements in processing efficiency, accuracy, and risk management through the adoption of AI-powered solutions.